Immigrant over- and under-education: The role of home country labour market experience - Piracha Matloob; Massimiliano Tani; Florin Vadean (IZA Journal of Migration, 2012)
Literature on the immigrant labour market mismatch has not explored the signal provided by the quality of home country work experience, particularly that of education-occupation mismatch prior to migration.We show that type of work experience in the home country plays a significant role in explaining immigrant mismatch in the destination country's labour market. We use the Longitudinal Survey of Immigrants to Australia and find that having been over-educated in the last job held in the home country increases the likelihood of being over-educated in Australia by about 45 percent. Whereas having been under-educated in the home country has an even stronger impact, as it increases the probability to be similarly mismatched in Australia by 62 percent.
Keywords: C34; J24; J61; 330; immigration; education-occupation mismatch; sample selection; Migranten; Arbeitsmigranten; Qualifikation; Arbeitsmarkt; Ungelernte Arbeitskräfte; Unterbeschäftigung; Matching; Australien